Real-world outcomes of anticoagulant prescription in anticoagulant-naïve octogenarian patients with non-valvular atrial fibrillation - Park, Sugeon; Kwon, Chang Hee (Journal of Cardiovascular Medicine and Cardiology, 2020)
Background and objectives: The clinical practice of anticoagulation in anticoagulant-naïve octogenarians with non-valvular atrial fibrillation (NVAF) has not been established in a real-world setting. We aimed to investigate the real-world prescription for anticoagulation and to compare the efficacy and safety of non-vitamin K antagonist oral anticoagulants (NOACs) and warfarin vs. no anticoagulation in anticoagulant-naïve octogenarian NVAF patients. Subjects and methods: From January 1, 2013 to August 31, 2015, we identified 89 consecutive newly detected NVAF patients aged ≥80 years. We retrospectively reviewed medical records until May 31, 2017 according to the differences in anticoagulation prescription (no anticoagulation, 39 patients; NOACs, 17; warfarin, 33). The efficacy outcome was stroke or systemic embolism. The safety outcome was total and major bleeding. Results: Stroke incidence did not differ significantly among the prescriptions (no anticoagulation, 2.41; NOACs, 3.55; and warfarin, 1.28 per 100 patient-years). Considerable incidence of major bleeding was observed in the anticoagulation groups (no anticoagulation, no events; NOACs, 12.11; and warfarin, 4.30 per 100 patient-years, p = 0.570). Total bleeding tended to be high in the NOAC and warfarin groups compared to no anticoagulation (no anticoagulation, 1.21; NOACs, 20.91; warfarin, 10.76 per 100 patient-years, p = 0.054). In the multivariable Cox proportional hazard model, previous bleeding history, warfarin and NOACs treatment were significant predictors for total bleeding. Conclusion: The occurrence of total and major bleeding was excessively high in the anticoagulation groups (NOACs or warfarin) compared to the no anticoagulation group. Future study is required to optimize anticoagulant regimen in octogenarian subjects.